The Body As Canvas As Picture: Bodypainting and its Implications for the Model - Jerrentrup, Maja Tabea (International Journal of Culture and Art Studies, 2020)
Body painting turns the body into a canvas – this frequently used phrase illustrates the challenge that body painting faces: It uses a three-dimensional surface and has to cope with its irregularities, but also with the model’s abilities, likes and dislikes. After giving an introduction to the art and categorizing its various types and contexts, the article focuses on the European body painting scene and on the role of the model within the scene. Although body painting can be very challenging for her – she has to expose her body and to stand still for a long time while getting transformed – models report that they enjoy the process and the result, even if they are not confident about their own bodies. A reason is that the “double staging“ – becoming a threedimentional work of art and then being staged for a photograph – remotes the body from the model and gives her the chance to see her painted body detached from herself. On the one hand, body painting closely relates to the body, on the other hand, it can help to overcome the body.